Enhancing the social innovation and green behavior of college students for sustainability: thinking solutions under the information cocoon - Xiaowei Dong (Discover Sustainability)
Abstract This study adopts a configuration perspective to examine how college students enhance their green behavior and social innovation tendency for sustainability by combining the information cocoon and thinking solutions from the complex-systematic-critical triangular thinking key proposed in this study. Using the fuzzy-set qualitative comparative analysis, we find four solutions that lead to high green behavior and seven solutions achieving high social innovation tendency for Chinese college students. Moreover, all the four paths to achieve high green behavior reappear in the thinking paths to realize high social innovation tendency, which are regarded as efficient paths. Our study offers a holistic understanding of the relationship between thinking of college students and sustainability manifesting as green behavior and social innovation tendency when considering the degree of information cocoons that they are facing, and yields useful insights for college students and higher educational institutions.